2014
DOI: 10.5808/gi.2014.12.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Legionellosis Drug Target Candidate Enzyme Phosphoglucosamine Mutase fromLegionella pneumophila(strain Paris): AnIn SilicoApproach

Abstract: The harshness of legionellosis differs from mild Pontiac fever to potentially fatal Legionnaire's disease. The increasing development of drug resistance against legionellosis has led to explore new novel drug targets. It has been found that phosphoglucosamine mutase, phosphomannomutase, and phosphoglyceromutase enzymes can be used as the most probable therapeutic drug targets through extensive data mining. Phosphoglucosamine mutase is involved in amino sugar and nucleotide sugar metabolism. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This was the reason behind the selection of B. cereus M4 metalloprotease (PDB ID: 1NPC). Results generated by secondary structure prediction tool SOPMA showed the abundance of coiled region (41.64%) indicated higher conservation and stability of the model 1NPC [66,67]. Information from PDBsum aided in determining the overall structural organization of proteins and predicting protein pockets for ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…This was the reason behind the selection of B. cereus M4 metalloprotease (PDB ID: 1NPC). Results generated by secondary structure prediction tool SOPMA showed the abundance of coiled region (41.64%) indicated higher conservation and stability of the model 1NPC [66,67]. Information from PDBsum aided in determining the overall structural organization of proteins and predicting protein pockets for ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…Results generated by secondary structure prediction tool SOPMA showed the enzyme is dominated by 43.3 % alpha helix and 33.04 % random coils along with 15.62 % extended strands and 8.04 % beta turns. The abundance of coiled region indicates higher conservation and stability of the model [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of coiled regions in the secondary structure prediction tool SOPMA results indicated that the models were significantly conserved and stable [ 130 , 131 ]. The PDBsum data helps establish the general structural arrangement of proteins and predict ligand-binding pockets.…”
Section: Discussionmentioning
confidence: 99%